1987
DOI: 10.1159/000261004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Enamel Fluoride Concentration and Dental Caries Experience

Abstract: Enamel biopsies for F analysis were performed on the mesial, buccal, distal and lingual surfaces of contralateral pairs of premolars extracted from 104 10- to 14-year-old children. Five successive etchings, each of 5 s duration, were carried out on the mesial and buccal surfaces with 2 M HClO4, and 5 successive etchings, each of 2 s duration, were performed on the distal and lingual surfaces using 0.5 M HClO4. The F concentrations were adjusted to standardized depths and the F concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The wide range of individual enamel fluoride val ues found in Icelandic children is in agreement with the results from a similar study [Aasenden et al, 1971], Although several samples contained a rather high fluoride concentration, a considerable fraction of study subjects had very low enamel fluoride con tents and the average and median values among Ice landic schoolchildren were below the levels reported from similar investigations in other populations [Bruun et al, 1975;Retief et al, 1987], As fluoride is virtually absent from the public water supply in Reyk javik and, according to a recent estimate, the average total daily intake of fluoride in schoolchildren does not exceed 0.4 mg [Sigurbergsdottir and Möller, 1984], the environmental exposure to fluoride is com paratively low [Becker and Bruce, 1981;Singer and Ophaug, 1986], Although drinking water and food remain an im portant source of fluoride [Ericsson, 1973;Ritömaa et al, 1974], the topical agents have proved to be as ef fective [Larsen et al, 1986] or even superior [Petersson, 1976] in increasing the fluoride content in sur face enamel. It is conceivable that Icelandic children who do not use fluoride dentifrices regularly and are not receiving other topical fluoride treatments have a surface enamel that is relatively deficient in fluoride.…”
Section: Discussionsupporting
confidence: 90%
“…The wide range of individual enamel fluoride val ues found in Icelandic children is in agreement with the results from a similar study [Aasenden et al, 1971], Although several samples contained a rather high fluoride concentration, a considerable fraction of study subjects had very low enamel fluoride con tents and the average and median values among Ice landic schoolchildren were below the levels reported from similar investigations in other populations [Bruun et al, 1975;Retief et al, 1987], As fluoride is virtually absent from the public water supply in Reyk javik and, according to a recent estimate, the average total daily intake of fluoride in schoolchildren does not exceed 0.4 mg [Sigurbergsdottir and Möller, 1984], the environmental exposure to fluoride is com paratively low [Becker and Bruce, 1981;Singer and Ophaug, 1986], Although drinking water and food remain an im portant source of fluoride [Ericsson, 1973;Ritömaa et al, 1974], the topical agents have proved to be as ef fective [Larsen et al, 1986] or even superior [Petersson, 1976] in increasing the fluoride content in sur face enamel. It is conceivable that Icelandic children who do not use fluoride dentifrices regularly and are not receiving other topical fluoride treatments have a surface enamel that is relatively deficient in fluoride.…”
Section: Discussionsupporting
confidence: 90%
“…These obser vations suggest that the equilibrium, or 'steady-state', data reflect the predominance of a different oral reservoir than is responsible for the second phase of salivary clearance curves. The existence of more than one oral fluoride res ervoir is, in fact, not surprising since fluoride has been found in plaque [see review of Tatevossian, 1990], in tooth enamel [see, for example, Mellberget al, 1985;Retief et al, 1987] and in various oral soft tissues [Jacobson et al, 1992;Tatevossian, 1978;Yao and Gron, 1970], It is possible that more than one reservoir site is in volved in the rate processes implied by the clearance curves of figure 1, as sums of exponentials with similar exponents can resemble a single exponential. However, the mean clearance data of table 1 show that, whatever their true complexity, the curves are fitted well by a model which assumes only one reservoir site [for more discussion 46 Duckworth/Stewart Saliva Fluoride from Mouthwashes of Constant NaF Content of the model see Duckworth and Morgan, 1991].…”
Section: Discussionmentioning
confidence: 99%
“…Of these studies, results have been equivocal. Many have failed to find a significant correlation [Candeli et al, 1970;Poulsen and Larsen, 1975;Retief et al, 1979] or found only a weak correlation [Mellberg et al, 1985;Retief et al, 1987]. In contrast, several workers have shown a positive association be tween these parameters [Mobley, 1981;Sakkab, 1984;Arends et al, 1985].…”
Section: Discussionmentioning
confidence: 99%
“…This technique of measuring the fluoride content of enamel by acid etch biopsy [van der Merwe et al, 1974] has found applications following both in vitro [Mellberg, 1980;Peterson et al, 1989] and in vivo [Reintsema et al, 1985;Hellwig et al, 1987] experi ments. A conclusive correlation between the fluoride content of enamel and its caries susceptibility has, however, not been shown [Retief et al, 1987], Animal caries models have been used to demonstrate the effi cacy of fluoride dentifrices since the 1960s and are well documented in the literature. Animal models are now, however, less widely used than in the past, and replacement methods are being urgently sought.…”
mentioning
confidence: 99%